2021
DOI: 10.3389/fcvm.2021.672745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Quality on the Risk of Emergency Room Visits in Patients With Atrial Fibrillation

Abstract: Background: We investigated the effect of particulate matter with aerodynamic diameter <2.5 μm (PM2.5) and meteorological conditions on the risk of emergency room visits in patients with atrial fibrillation (AF) in Beijing, which is considered as a monsoon climate region.Methods: In this case-crossover design study, medical records from patients with AF who visited the Critical Care Center in the Emergency Department of Anzhen Hospital from January 2011 through December 2014 and air quality and meteorol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…A study conducted by Liang et al in Beijing also showed that as time passed, the AF risk of patients visiting the emergency room increased. On lag6, there was a positive correlation between the air pollutants and AF [40]. The results of this study showed evidence that air pollutants are risk factors for the occurrence of AF.…”
Section: Discussionsupporting
confidence: 52%
“…A study conducted by Liang et al in Beijing also showed that as time passed, the AF risk of patients visiting the emergency room increased. On lag6, there was a positive correlation between the air pollutants and AF [40]. The results of this study showed evidence that air pollutants are risk factors for the occurrence of AF.…”
Section: Discussionsupporting
confidence: 52%
“…40 The effects of PM 2.5 seemed to be heightened in settings of intense solar geomagnetic activity 41 and monsoon climates. 42 This highlights the intricate relationship between meteorologic conditions and air pollution in influencing AF presentation. Moreover, secondary compounds such as…”
Section: Figure 2 Exposure-response Relationship Curves Between Fine ...mentioning
confidence: 98%
“…40 The effects of PM 2.5 seemed to be heightened in settings of intense solar geomagnetic activity 41 and monsoon climates. 42 This highlights the intricate relationship between meteorologic conditions and air pollution in influencing AF presentation. Moreover, secondary compounds such as NO 3 − , SO 4 2− , and NH 4 + , which constitute a significant portion of atmospheric PM 2.5 also exhibit seasonal fluctuations, 40 and likely carry a significant role.…”
Section: Ambient Environmentmentioning
confidence: 98%
“…We screened the full text of the 12 remaining records, with 1 of them being excluded due to a study design that was not suitable for our inclusion criteria, and 2 of them did not provide usable data. Nine remaining studies were included in our systematic review [28][29][30][31][32][33][34][35][36], and five of them were included in our meta-analysis (Fig 1) [28,29,32,34,35]. All the data required for analysis were reported or visualized, and no imputation of data was made during the extraction process.…”
Section: Study Selectionmentioning
confidence: 99%
“…All the data required for analysis were reported or visualized, and no imputation of data was made during the extraction process. The association parameters for the following studies were digitized from graphs: Jin (2022) [30], Lee (2019) [32], Liang (2021) [33], Zanobetti (2014) [35], and Zheng (2018) [36].…”
Section: Study Selectionmentioning
confidence: 99%